If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + 7 = 2z + 13 Reorder the terms: 7 + 5z = 2z + 13 Reorder the terms: 7 + 5z = 13 + 2z Solving 7 + 5z = 13 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. 7 + 5z + -2z = 13 + 2z + -2z Combine like terms: 5z + -2z = 3z 7 + 3z = 13 + 2z + -2z Combine like terms: 2z + -2z = 0 7 + 3z = 13 + 0 7 + 3z = 13 Add '-7' to each side of the equation. 7 + -7 + 3z = 13 + -7 Combine like terms: 7 + -7 = 0 0 + 3z = 13 + -7 3z = 13 + -7 Combine like terms: 13 + -7 = 6 3z = 6 Divide each side by '3'. z = 2 Simplifying z = 2
| -67=-19-6x | | -16x=192 | | 56=26n | | H(t)=16t^2-32t+5 | | 5b-18= | | 2(-5g+6)= | | -4(w-7)+9w+3= | | 7x+9x-80=60-4x | | h(t)=-16t^2+64t+384 | | -12=z(3) | | 4x+10=51 | | -3/4x+1/8=5x | | x/6+5=1/3-x | | -1x+1y-7=0 | | 2x+8x+16=25 | | 2x+8x+16=25 | | 2x+8x+16=25 | | -1x+1y-7=0 | | -10+6b=8-4b | | (v-5)(7v-35)=0 | | h(t)=-16t^2+64+384 | | 2.2(0.5y+9)-3.1y=-0.2 | | 11=-12-q | | 21+7d+3d-15=13d+15-3d-9 | | F(x)=.52x+5040 | | F(x)=.52x+5040 | | z^2+7=0 | | sqrt(2x-1)=7 | | 3a+2b+2(5a)= | | x-x=14 | | sqrt(2t-1)=7 | | 210=-6(-3-4x) |